2021
DOI: 10.1002/adsc.202101361
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Ammonium Cation‐Assisted Hydropyridylation of Ketone‐Activated Alkenes: Experimental and Computational Mechanistic Studies

Abstract: This work describes an electrochemical ammonium cation enabled hydropyridylation of ketone‐activated alkenes under metal‐ and exogenous reductant free conditions giving access to β‐pyridyl ketones, through dual proton‐coupled electron transfer and radical cross‐coupling. It features a broad substrate scope and allows a gram‐scale synthesis. Ammonium chloride plays various roles in this transformation such as the hydrogen donor, the protonation reagent, and electrolyte. In particular, various experiments and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…Moreover, the reduction electrode potentials of 1e (E onset = −1.45 V versus Ag/AgCl) and 2a (E onset = −1.27 V versus Ag/AgCl) in the presence of NH 4 OAc were compared, and the result confirms that the protonated 2a should be preferentially reduced on the surface of the cathode ( Figure 3 A). Furthermore, the square-wave voltammetry (SWV) experiments of 1e and 2a were performed in the presence of NH 4 OAc to further explore the electron transfer of the reaction mechanism ( Figure 3 B) ( Yang et al., 2022 ; Peters et al., 2019 ; Liu et al., 2020 ). The peak splits significantly with the frequency change, which is consistent with the process of proton-coupled electron transfer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the reduction electrode potentials of 1e (E onset = −1.45 V versus Ag/AgCl) and 2a (E onset = −1.27 V versus Ag/AgCl) in the presence of NH 4 OAc were compared, and the result confirms that the protonated 2a should be preferentially reduced on the surface of the cathode ( Figure 3 A). Furthermore, the square-wave voltammetry (SWV) experiments of 1e and 2a were performed in the presence of NH 4 OAc to further explore the electron transfer of the reaction mechanism ( Figure 3 B) ( Yang et al., 2022 ; Peters et al., 2019 ; Liu et al., 2020 ). The peak splits significantly with the frequency change, which is consistent with the process of proton-coupled electron transfer.…”
Section: Resultsmentioning
confidence: 99%
“…However, we found that the pyridylation of electron-deficient quinolines cannot be achieved by adopting the previous protocol. Inspired by the mechanism of electrochemical ammonium cation-assisted ketone-activated alkene hydrogenation of pyridine to obtain β-pyridyl ketones ( Yang et al., 2022 ). Herein, we developed the first straightforward and practical strategy for the pyridylation of electron-deficient quinolines aided by NH 4 + in an undivided cell via the dual PCET followed by the radical cross-coupling ( Scheme 1 D).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the preliminary findings and previous reports, 6,7 a probable mechanism for convergent paired electrolysis-induced hydrophosphorylation of chalcone is speculated and outlined in Scheme 3. First, the preferential cathode reduction of 1a delivers radical anion intermediate A , which undergoes proton and charge transfer with 1b to yield carbon radical intermediate C and anion intermediate B .…”
mentioning
confidence: 77%
“…5 We hypothesized that the lower reduction potential of ketone-activated alkenes would preferentially undergo reductive protonation to generate carbon radical species III , which would then be cross-coupling with phosphorus radical V generated by the anodization of diarylphosphorous to obtain the desired product (Scheme 1(c)). 6 We anticipate that the hydrophosphorylation of ketone-activated alkenes is mediated by a convergent paired electrolysis strategy with unconventional radical sites, enabling the avoidance of metal catalysts, high temperatures, and external redox reagents. Here, we wish to report a straightforward and practical strategy for hydrophosphorylation of electron-deficient alkenes and alkynes to access γ-ketophosphine oxides, enabled by a convergent paired electrolysis in the absence of metal, base, and redox reagent conditions (Scheme 1(d)).…”
mentioning
confidence: 99%
“…In our previous study, we have achieved the C3 pyridylation of quinoxalin-2(1H)-ones with readily available cyanopyridines under electrochemical conditions by employing 1,1,1,3,3,3-hexafluoropropan-2-ol (HFIP) as the protonation reagent ( Wen et al., 2021 ). Nonetheless, the pyridylation of electron-deficient quinolines cannot be realized by adopting the previous protocol ( Yang et al., 2022 ).…”
Section: Before You Beginmentioning
confidence: 99%